ANALISIS KUALITAS PELAYANAN TERHADAP LOYALITAS NASABAH BPR ARGO DANA UNGARAN - Andi Lukman, 08.05.51.0017; wuryan, Sophiyanto (Students Journal of Economic and Management, 2012)
The purpose of this study was to analyze the influence of the quality of services consisting of physical (tangible), reliability (reliability), responsiveness (responsiveness), insurance (assurance)and empathy (empathy) towards customer loyalty BPR ARGO DANA UNGARAN. Populations and samples in this study were clients of rural banks amounted Ungaran ARGO DANA 100 people. Retrieval technique is the technique of random sample (random / probability). Type of data is primary. Methods of data collection using questionnaires. Analysis technique used is multiple regression with SPSS 13 program . Key Words: Physical Evidence, Reliability, Power Response, Security, Empathy and Customer Loyalty.